Comparison of fluoroscopy and fluoroscopy-based 2D computer navigation for iliosacral screw placement: a retrospective study - Madeja, Roman; Pometlová, Jana; Osemlak, Pawel; Voves, Jiří; Bialy, Lubor; Vrtková, Adéla; Pleva, Leopold (European journal of trauma and emergency surgery, 2022)
PURPOSE: Treatment of pelvic fractures is often complicated. Here, we intended to evaluate the intraoperative benefits of using 2D computer navigation when compared with traditional fluoroscopy on X-ray burden, surgical time and screw placement accuracy. METHODS: In this study, we retrospectively evaluated the records of 25 patients who underwent osteosynthesis of a posterior pelvic fracture using fluoroscopy at the University Hospital Ostrava, Czech Republic between 2011 and 2019, and 32 patients from the same department and period in whom 2D computer navigation was used. RESULTS: Intraoperative X-ray burden was significantly lower in the group with 2D computer navigation (median 650 vs 1024 cGy/cm2), as was the duration of the surgery (41 vs 45 min). This was most obvious where two screws were inserted (X-ray dose of 994 vs 1847 cGy/cm2 and 48 vs 70 min, respectively). Correction of the path for wire placement after the original drilling was necessary in 2 patients (6%) from the 2D computer navigation group and 15 patients from the fluoroscopy group (60%). Still, no malposition of the screws nor dislocation of the posterior pelvic segment after 12 months was observed in any patient of either group; of complications, only three superficial infections in the 2D navigation group and 2 in the fluoroscopy group were observed. CONCLUSION: 2D computer navigation is a safe and accurate method for placement of screws during posterior pelvic fracture osteosynthesis, associated with lower intraoperative radiation burden and shorter surgical times compared to standard fluoroscopy, especially if two screws are inserted.
Keywords: Computers; Fluoroscopy; zobrazování trojrozměrné; kostní šrouby; Retrospective Studies; retrospektivní studie; lidé; chirurgie s pomocí počítače; fraktury kostí; Surgery, Computer-Assisted; Fracture Fixation, Internal; Imaging, Three-Dimensional; Fractures, Bone; Humans; vnitřní fixace fraktury; fluoroskopie; počítače; Bone Screws